Clinical study and management of pseudocyst of pancreas - Babu, G. Rajashekara; Venkatesh, Sahanashree; K., Ramakrishnan; Jain, Parvesh (International Surgery Journal, 2017)
Background: Pancreatic pseudocysts can occur as a complication of acute or chronic pancreatitis. Understanding of pseudocysts has changed with times due to advancement in radiology and introduction of new treatment modalities. This study was done to access clinical features etiology and various managements for pseudocyst in a tertiary care hospital. Methods: It is a prospective study of 40 adult patients admitted in Victoria and Bowring and Lady Curzon Hospital, attached to Bangalore Medical College and Research Institute, Karnataka, India from January 2015 to December 2016. Results: Pseudocysts are more common in males. The commonest etiology associated was alcohol. Ultrasound was the basic radiological investigation done in all patients followed by CECT abdomen. Complications associated with pseudocyst were Gastric outlet obstruction and ascites. Internal drainage was done in most of the patients. Post drainage complications included infection which was managed by antibiotics and endoscopic drainage in case of recollection. Pain was most important post-operative complication. Endoscopic drainage is being preferred as it is less invasive, has a high long term success rate, has shorter duration of hospital stay and more patient comfort. Conclusions: Pseudocyst of pancreas is most commonly seen in males probably because of alcoholism. Clinical presentation can be varied, with pain abdomen being the most common complaint followed by, nausea vomiting. Initial management consists of supportive care and if the symptoms persist and complications develop surgical drainage was the most common management modality. Newer modalities of treatments like endoscopic intervention have an added advantage of lesser pain, shorter duration of hospital stay and recurrence.